2008
DOI: 10.1002/anie.200705237
|View full text |Cite
|
Sign up to set email alerts
|

Perylene Bisimide Dimers as Fluorescent “Glue” for DNA and for Base‐Mismatch Detection

Abstract: Perylene-3,4:9,10-tetracarboxylic acid bisimide ("PB") and its derivatives are applied as fluorescent dyes in organic materials owing to their excellent photochemical stability as well as the high fluorescence quantum yields. [1,2] The strong hydrophobic stacking interactions between the PB chromophores make this dye an important building block for functional supramolecular architectures. [1,3] Based on these properties, PB in the dimeric form should be also of potential interest as a probe for fluorescent DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 36 publications
6
94
0
Order By: Relevance
“…Indeed, upon binding the 3′ polyadenine tract of our constructs, the complementary strands would be expected to exhibit a relatively small effect on the rapid assembly dynamics and kinetics of the terminal PTCDI DNA base surrogates. Overall, Oligo1, Oligo2, and Oligo3 represented reasonable general analogues for the diverse class of perylene-modified oligonucleotides previously investigated with photophysical techniques in solution 16,17,19 and electrochemical techniques at solid substrates. 26 We characterized Oligo1, Oligo2, and Oligo3 with UV−vis spectroscopy (Figure 2), observing a clear evolution in the molecules' spectra as the number of PTCDI moieties increased.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Indeed, upon binding the 3′ polyadenine tract of our constructs, the complementary strands would be expected to exhibit a relatively small effect on the rapid assembly dynamics and kinetics of the terminal PTCDI DNA base surrogates. Overall, Oligo1, Oligo2, and Oligo3 represented reasonable general analogues for the diverse class of perylene-modified oligonucleotides previously investigated with photophysical techniques in solution 16,17,19 and electrochemical techniques at solid substrates. 26 We characterized Oligo1, Oligo2, and Oligo3 with UV−vis spectroscopy (Figure 2), observing a clear evolution in the molecules' spectra as the number of PTCDI moieties increased.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…[16] We showed that perylene bisimide stacks as a chiral oligochromophore inside the double helical framework. [17] Moreover, we [9,17,19] and others [20] have shown that perylene bisimide triggers the reversible aggregation of complete DNA duplexes, hairpins, and dumbbells, yielding electronically conjugated nanostructures.…”
Section: Introductionmentioning
confidence: 84%
“…However, it is important to point out that in the absence of adjacent guanines the fluorescence intensity of PBI is still sufficient to obtain clear fluorescence readout for DNA assemblies [18][19][20] and bioanalysis. [16,17] With respect to the power of perylene bisimide in DNA-based nanostructuring it looked promising to design a new DNA base substitution based on the perylene bisimide scaffold that overcomes the problem of photoinduced guanine oxidation by maintaining the fluorescence quantum yield of PBI in guanine-poor sequences. Two strongly electron-donating substituents at the core of the chromophore should reduce the electron deficiency significantly and thus may prevent photoinduced guanine oxidation.…”
Section: Synthesis Of the Apbi Dna Building Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional methods that use radioactive [ 32 P]-labeled nucleic-acid (NA) probes or the polymerase-chain reaction (PCR) coupled with molecular fluorophore assays offer high sensitivity of detection, but they suffer from several drawbacks (e.g., complex handling procedures, easy contamination, high cost and lack of portability) [19][20][21][22]. Recently, great efforts have been made to develop biotechnologies to improve the sensitivity, the selectivity and the ease of operation for NA analysis [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%